Real-time HIL-simulation of power electronics - Maas, Jürgen; Schulte, Thomas; Graf, C.; Weise-Emden, J.
In modern vehicles, electrical drives and power electronics are used to control a large variety of different applications. To operate these components electronic control units have to be designed and tested. To validate the software of the electronic control units hardware-in-the-loop simulation is a todaypsilas standard method. Hardware-in-the-loop simulation always comprises a real-time simulation of the plant, including actuator and sensor models. In case of an electronic circuit the plant consists of passive components like capacitors and inductors, usually assumed to be linear, and semi-conductors with nonlinear and discontinuous behavior. The following paper suggests classification criteria and compares different methods for real-time simulations of electronic circuits considering switching events. For evaluation theoretical considerations as well as simulation results are presented concerning differences in approaches.